Inhibition of Cancer Cell Proliferation and Antiradical Effects of Decoction, Hydroalcoholic Extract, and Principal Constituents of Hemidesmus indicus R. Br. (6th March 2015) - Statti, Giancarlo; Marrelli, Mariangela; Conforti, Filomena; Spagnoletti, Antonella; Tacchini, Massimo; Fimognari, Carmela; Brognara, Eleonora; Gambari, Roberto; Sacchetti, Gianni; Guerrini, Alessandra
<x xml:space="preserve">Abstract</x> Indian Sarsaparilla (Hemidesmus indicus R. Br.) is widely used in Indian traditional medicine. In the present work, we explored the effects of decoction, traditional Ayurvedic preparation, and hydroalcoholic extract, a phytocomplex more traditionally studied and commercialized as food supplement in western medicine, from the roots as possible source of chemicals with new functional potential linked to their nutritional uses. The antiproliferative and antioxidant properties were assayed. To test antiproliferative affects, different cancer cell lines, growing both as monolayers (CaCo2, MCF‐7, A549, K562, MDA‐MB‐231, Jurkat, HepG2, and LoVo) and in suspension (K562 and Jurkat) were used. The decoction showed strong activity on HepG2 cells, while the hydroalcoholic extracts were active on HepG2, LoVo, MCF‐7, K562, and Jurkat cell lines. Weak inhibition of cancer cell proliferation was observed for the principal constituents of the preparations: 2‐hydroxy‐4‐methoxybenzaldehyde, 2‐hydroxy‐4‐methoxybenzoic acid, and 3‐hydroxy‐4‐methoxybenzaldehyde that were tested alone. The antiradical activity was tested with 2, 2‐diphenyl‐1‐picrylhydrazyl and 2, 2′‐azinobis(3‐ethylbenzothiazoline‐6‐sulfonic acid)diammonium salt tests and inhibition of nitric oxide production in lipopolysaccharide‐stimulated RAW 264.7 macrophages. Interesting result has also been obtained for hydroalcoholic extract regarding genoprotective potential (58.79% of inhibition at 37.5 µg/mL). Copyright © 2015 John Wiley & Sons, Ltd.